Optimization of ?-amylase production by Bacillus sp using response surface methodology - Tanyildizi, MS; Özer, D; Elibol, M (Elsevier Sci Ltd, 2005)
The combined effects of macronutrients of media on alpha-amylase production by Bacillus sp. were studied using response surface methodology. A 2(2) full-factorial central composite design was chosen to explain four medium constituents, viz. starch, glycerol, yeast extract (YE) and peptone, and to analysis of the results. This procedure limited the number of actual experiments performed while allowing for possible interactions between four components. The P-value of the coefficient for quadratic effect of glycerin concentration was < 0.0001, suggesting that this was the principal experimental variable having the greatest effect on the production of alpha-antylase. It was found that YE had no effect on alpha-amylase production. The optimal combinations of media constituents for maximum alpha-amylase production were determined as 17.58 g/l starch, 12.37% (v/v) glycerin, 8.77 g/l peptone and 0.00 g/l YE. (c) 2004 Elsevier Ltd. All rights reserved.
Keywords: alpha-amylase; enzyme production; response surface methodology; Bacillus sp.